Algebra 2

Solve by using the substitution method.

x = 3y - 1
x + 2y = 9



Hi,

When you have a pair of equations as in this problem, the method of substitution is to find a value for one of the variables in one equation and then substitute that value into the second equation. In your problem, the way the first equation is written you already know a value for x, it is 3y - 1. Thus stustitute, (that is replace) this value for x into the second equation. The second equation is

x + 2y = 9 and hence, replacing x by 3y - 1 gives (3y - 1) + 2y = 9

Simplify this exprression by adding 1 to each side and you get

3y + 2y = 10 That is 5y = 10 or y = 2

Now that you know y you can find x since the first equation tells you that x = 3y - 1. Thus x = 3  2 - 1 = 5.

Penny

Go to Math Central

To return to the previous page use your browser's back button.